Influence of Vertical Loading on Behavior of Laterally Loaded Foundation Piles: A Review - Qiang Li; Luke J. Prendergast; Amin Askarinejad; Ken Gavin (Journal of Marine Science and Engineering, 2020)
The majority of installed offshore wind turbines are supported on large-diameter, open-ended steel pile foundations, known as monopiles. These piles are subjected to vertical and lateral loads while in service. In current design practice, interaction of vertical and lateral loads are not considered, rather piles are designed to resist vertical and lateral loads independently. Whilst interaction effects are widely studied for shallow foundations, the limited research on this topic for pile foundations often produces conflicting results. This paper reviews the research of the influence of vertical loading on the lateral response of pile foundations under combined loads, from the perspective of analytical research, numerical research, and experimental research from tests performed on 1-g (gravitational acceleration) model, centrifuge, and full-scale piles. The potential reasons for the differences among the results of previous research are discussed. Some guidance for future research on the effect of vertical loads on the lateral response of piles is provided.